FOSTERING OR HINDERING CREATIVITY AT WORK? MODERATING ROLE OF PROACTIVE PERSONALITY TOWARD SUPPORT AND MEANINGFULNESS - Handrio Adhi Pradana; Zulfa Uliani (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
This study aims to investigate the main effects and moderating role of proactive personality on the influence of perceived organizational support and meaning of work on creativity. Data was collected from 155 professionals and knowledge workers in information technology companies with non-probability sampling using snowball technique. This study uses hierarchical regression analysis with SPSS 22 software to test hypotheses. Results revealed that perceived organizational support and meaning of work have significant positive effect on employee creativity. Moderating effect of proactive personality has successfully amplified meaning of work on creativity. An interesting and unexpected finding is that proactive personality moderate significant negative effect of perceived organizational support on creativity. That is, high level of proactivity actually weakens relationship between perceived organizational support and creativity. The finding extends creativity literature related to social exchange theory. Practical implications are also discussed in this article. Keywords: creativity, perceived organizational support, meaning of work, proactivity